Poziom rozwoju podmiotowości jako jeden z zasobów dobrostanu zawodowego w działalności kierowniczej = Agency as a resource of job-related well-being in managerial work - Berezovskaa, Regina A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study addresses the improving of job-related well-being among Russian managers and analyzes the role of agency ("subjectivity") in this process. As a criterion of occupational well-being is considered a self-assessment of the level of professional demand which is defined as meta-system of person's subjective attitudes to him/herself as significant professional for others.
Keywords: psychologia zdrowia zawodowego; podmiotowość; dobrostan zawodowy; przeżywania subiektywnego znaczenia wykonywanego zawodu; podejście zasobowe; działalność menedżerska; occupational health psychology; agency (subjectivity); job-related well-being; professional demand; resource approach; managerial work